Cardiovascular diseases and risk factors in kidney transplant candidates - Kocabaş, Umut (The European Research Journal, 2021)
Objectives: Cardiovascular diseases and risk factors are associated with adverse cardiac events following kidney transplant. Therefore, pre-transplant evaluation of cardiovascular diseases and risk factors is important for determining the cardiac risk. The objective of this study is to determine the prevalence of cardiovascular diseases and risk factors in kidney transplant candidates. Methods: This is a single-center and observational study which includes 174 end-stage renal disease patients (male: 55.2% and mean age: 49 ± 13 years) who underwent kidney transplant. Preoperative clinical characteristics, cardiovascular diseases and risk factors of the patients were examined retrospectively. Results: The study population had multiple cardiovascular risk factors such as hypertension (66.7%), diabetes (28.2%), dyslipidemia (29.9%) and smoking (30.5%) in the evaluation conducted prior to kidney transplant. The most common cardiovascular diseases were detected as congestive heart failure (10.9%) and coronary artery disease (8.6%). The rate of the patients who underwent myocardial revascularization (percutaneous coronary intervention or coronary artery bypass grafting) before kidney transplant was 6.9%. The patients’ mean left ventricular mass index was 114 ± 32 g/m2, and 55.5% of the study population had left ventricular hypertrophy. Conclusions: In our study, the prevalence of cardiovascular diseases and risk factors in the patients who underwent kidney transplant was found to be high.